Consistency of Practice and the Normative Legal Implications of Cancelling Practices from the Perspective of Ahkam Interpretation: An Analysis of QS. Muhammad Verses 33-35 - Tiara Rahma; Risa Siti Fadilah (Program Pascasarjana UIN Sumatera Utara Medan, 2024)
This study examines the principle of consistency in deeds through an analysis of legal interpretation (tafsir ahkam) of QS. Muhammad verses 33-35. The main focus of this research is to explore the meaning of the prohibition on canceling deeds in the middle of their implementation and the theological and social consequences that arise. Using qualitative methods through a library research approach, this study examines the interpretation of these verses from various classical and contemporary tafsir literature. The results show that QS. Muhammad: 33 gives a clear command for believers to obey Allah and His Messenger and strictly prohibits the destruction of the reward of deeds through inconsistency or doubt. Verse 34 provides a warning to those who hinder the path of Allah, while verse 35 provides a motivational guarantee for believers not to be weak in the struggle. The implications of this finding emphasize that canceling deeds is not merely an individual failure, but has a psychological impact on mental resilience and a social impact on community integrity. The relevance of this study in the modern context is applied to discipline in education, careers, and social struggles.